A Different Approach to Inflection Points Detection in L-Shape Curves - Alexandra BAICOIANU; Bianca A. LIXANDRU (Communications of International Proceedings, 2020)
This paper is organized around the problem of detecting the inflection point in a L-shaped curve. Nowadays, this problem is often encountered both in academic environment and in real situations, being found in fields such as engineering, mathematics and acoustics. This research study extends two specific procedures for detecting the inflection point in L-shaped curves: triangle method and optimal regularization method. A number of different experiments have been used to determine and recommend which method is superior and in which situations. We defined heuristics for which we defined an adaptive way of working given by the curve offered as input. Our research is focused on making both correct and efficient calculations, using parallel computation for example. In the following sections we will present the simplification of the curve, the methods, their results, the comparison between the two methods and all the conclusions.
Keywords: Inflection Point; SVD; L-Shaped Curve; Triangle Method; Simplified Curve; Optimal Regularization Method; Adaptive Algorithms.